Role of light in freezing tolerance of wheat - Janda, Tibor; Pap, Mátyás; Szalai, Gabriella (Acta Biologica Szegediensis, 2008)
During the frost hardening of wheat plants light intensity is a key factor in the development of frost tolerance, and several processes, including lipid metabolism, antioxidant activity, polyamine synthesis and salicylic acid signalling, may also contribute to light-enhanced freezing tolerance. The results suggest that there are at least two type of receptors, one cold-and one light-dependent, which induce signal transduction processes leading to freezing tolerance.